Karyotypes of Several Frog Species from Peninsular Malaysia - Kuramoto, M.; Yong, Hoi Sen (Herpetologists League, 1992)
Karyotypes of 11 species of peninsular Malaysian frogs belonging to the genera Leptobrachium (Pelobatidae), Amolops, Rana (Ranidae), Philautus, Polypedates, Rhacophorus (Rhacophoridae), and Microhyla (Microhylidae) are described. Chromosome numbers of L. hendricksoni (2N = 24) and A. larutensis (2N = 24) differed from those previously reported in the two genera (2N = 26). The karyotype of Rana blythii (2N = 24) resembled reported karyotypes of R. macrodon and R. magna, suggesting their close relationships. Microhyla butleri had 2N = 22 chromosomes, which is the first record of this number for the genus. The karyotype of the genus Philautus (2N = 26) was described for the first time in P. asper.